On Response Bias in the Face Congruency Effect for Internal and External Features - Günter Meinhardt; Bozana Meinhardt-Injac; Malte Persike (Frontiers in Human Neuroscience, 2017)
Some years ago Cheung et al. (2008) proposed the complete design (CD) for measuring the failure of selective attention in composite objects. Since the CD is a fully balanced design, analysis of response bias may reveal potential effects of the experimental manipulation, the stimulus material, and/or attributes of the observers. Here we used the CD to prove whether external features modulate perception of internal features with the context congruency paradigm (Nachson et al., 1995; Meinhardt-Injac et al., 2010) in a larger sample of N = 303 subjects. We found a large congruency effect (Cohen's d = 1.78), which was attenuated by face inversion (d = 1.32). The congruency relation also strongly modulated response bias. In incongruent trials the proportion of “different” responses was much larger than in congruent trials (d = 0.79), which was again attenuated by face inversion (d = 0.43). Because in incongruent trials the wholes formed by integrating external and internal features are always different, while in congruent trials same and different wholes occur with the same frequency, a congruency related bias effect is expected from holistic integration. Our results suggest two behavioral markers of holistic processing in the context congruency paradigm: a performance advantage in congruent compared to incongruent trials, and a tendency toward more “different” responses in incongruent, compared to congruent trials. Since the results for both markers differed only quantitatively in upright and inverted presentation, our findings indicate no change of the face processing mode by picture plane rotation. A potential transfer to the composite face paradigm is discussed.